A Clinical Case Report of Complete Dentures Using Resilient Denture Liners - Taguchi, Norihiro (Nihon Hotetsu Shika Gakkai Zasshi, 2004)
Patients: A man (68 years total edentulous) visited us because of masticatory soreness around the mandible. He also suffered from frequent fracture of the dentures.As the poor fitting and severe absorption of the mandible area was considered to be the main cause of the trouble, soft denture lining materials were used. After trying different types of soft denture liners over the new acrylic base dentures, the dentures were finally relined with fluoroelastomer. Discussion: The condition was good and the patient was very satisfied with the lined dentures.The soft liner contributed to the improvement of the QOL of the edentulous patient. Conclusion: The use of soft liner was effective for this difficult edentulous case. This case concerns the guideline for the relining of soft liners.